Learning Addition and Subtraction of Fractions Through the use of Indigenous Materilas: The Case of Dumagat Elementary Students - Faustino, Heidi Lynn (Archīum Ateneo, 2021)
Poor numeracy among students has been an alarming problem not only in the Philippines but also throughout the world. It incapacitates a person in dealing with daily activities especially with complex mathematical demands of life. The learning of fraction concepts and basic operations has been especially problematic. Strategies that ensure students do benefit from the mathematics curriculum must be in place. One way of teaching mathematics that increases learning opportunities is through the use of materials with which students are familiar. Mathematical tools such as well-crafted indigenous materials, if properly used, allow students to be actively engaged in learning mathematics and deepen their understanding of mathematics (SEI-DOST & MATHTED, 2011). With these in mind, this qualitative study investigated the benefits of using indigenous materials in learning addition and subtraction of fractions. Bruner’s (1966) ‘enactive-iconic-symbolic’ representation theory and Realistic Mathematics Education (RME) served as the frameworks for this study. Twenty-one Dumagat students from Grades 4, 5, and 6 were taught addition and subtraction of fractions first by using the indigenous materials, then by using pictorial representations, and finally by using the relevant mathematical symbols. An in-depth analysis of the worksheets and post-test revealed that there is evidence of learning among students since they achieved some learning competencies prescribed in the K to 12 Basic Education Curriculum. Results of the study showed that the specially designed lessons on addition and subtraction of fractions using indigenous manipulative materials facilitated students’ transition to the symbolic mode of representation by only some students. There is also evidence that the use of indigenous materials contributed to the high levels of motivation exhibited by the Dumagat students throughout the learning sessions. v Recommendations for further research, improvement of the IP school curriculum, and enhancement of teaching practices to create culturally sensitive mathematics classrooms are proposed.